Positioning student affairs for sustainable change : achieving organizational effectiveness through multiple perspectives - Kuk, Linda, 1950-; Banning, James H.; Amey, Marilyn J. (Stylus Publishing, LLC, 2010)
"As student affairs organizations have grown and become increasingly complex in order to meet new demands, they have often emphasized the expansion of their missions to the detriment of focusing on understanding their roles in relationship to other units, to reviewing their cultures and structures, and to considering how they can improve their effectiveness as organizations. This book provides the tools for organizational analysis and sustainability. Intended for practitioners, graduate students, interns and student affairs leaders, this book presents the key ideas and concepts from business-oriented organizational behavior and change theories, and demonstrates how they can be useful in, and be applied to, student affairs practice -- and, in particular, how readers can use these theories to sustain change and enhance their organization's ability to adapt to complex emerging challenges. At the same time it holds to values and perspectives that support the human dimension of organizational life"--Provided by publisher.